Assessing the impact of sustainability report disclosures and CEO attributes on the Indonesian energy sector: implications for capital market performance - Ayi Ahadiat; Amjad Shamim; Habibullah Jimad; Fajrin Satria Dwi Kesumah (Cogent Business & Management, 2024)
The growth of the world energy market is experiencing a slowdown moment in line with the decline in demand due to the COVID-19 pandemic. While Indonesia has the potential for energy resources and natural resources which are very diverse and abundant, on the one hand, it has not been utilized optimally. This study aims to analyze the impact of general sustainability report disclosures and CEO attributes of Indonesian energy companies on company value, measured using Tobin's Q indicators. The analysis is based on GRI standards for sustainability reports, CEO education levels, and CEO affiliation relationships, with control variables including ROE, firm size, leverage, and asset growth. This study uses annual report data and sustainability reports for every Indonesian energy company listed on the Indonesian Stock Exchange for the past four years. The estimation model used in the analytical method is multiple linear regression analysis. The results of this study indicate that on average Indonesian energy companies have general disclosures on sustainability reports that have a negative effect on Tobin's Q indicators, the education level of the CEO has a positive effect on the Tobin's Q indicators, and the CEO's affiliation relationship which has no effect on the Tobin's Q indicators.
Keywords: G20; M12; Q28; Q43; Q56; 650; Indonesia energy companies; sustainability report; global reporting initiative (GRI; ); corporate value; CEO education level; CEO affiliate Relations